THE INTERNAL CONTROL SYSTEM OF BANKS - Bibicheva, Tatiana (2019)
The banking system has always played an important role in society as a financial intermediary and as a storage of public and private savings. The key element of existence of a bank is trust of society. The effectiveness increase of banking control and especially the internal one is the most important condition of construction of reliable banking system, which is deserve confidence of investors. Thereby, the aim of this bachelor thesis is to investigate the role of internal control in bank management in Russia using a case study of a locally important bank. The practical part refers to evaluation of activity of specific Kazakh bank in Omsk city in Russia. The methodologies used during the research process are observation and comparison of actual qualitative and quantitative data with regulation and analysis of provided documents.